Characterizing solute hydrogen and hydrides in pure and alloyed titanium at the atomic scale - Chang, Y; Breen, AJ; Tarzimoghadam, Z; Kürnsteiner, P; Gardner, H; Ackerman, A; Radecka, A; Bagot, PAJ; Lu, W; Li, T; Jägle, EA; Herbig, M; et al. (Elsevier, 2018)
Ti and its alloys have a high affinity for hydrogen and are typical hydride formers. Ti-hydride are brittle phases which probably cause premature failure of Ti-alloys. Here, we used atom probe tomography and electron microscopy to investigate the hydrogen distribution in a set of specimens of commercially pure Ti, model and commercial Ti-alloys. Although likely partly introduced during specimen preparation with the focused-ion beam, we show formation of Ti-hydrides along α grain boundaries and α/β phase boundaries in commercial pure Ti and α+β binary model alloys. No hydrides are observed in the α phase in alloys with Al addition or quenched-in Mo supersaturation.